1994
DOI: 10.1097/00006842-199407000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and retrospectively reported antecedents of alexithymia.

Abstract: Two experiments were conducted in order to examine the relationship between alexithymia and: 1) family environment; 2) discomfort and ambivalence experiencing and expressing emotion; and 3) dissociation. Research participants in both experiments were college students. We examined the ability to identify and communicate emotion using the Toronto Alexithymia Scale. In Experiment 1, we found that alexithymia was significantly correlated with ambivalence concerning expression of emotion (measured using the Ambival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
101
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(120 citation statements)
references
References 18 publications
15
101
0
4
Order By: Relevance
“…Kérdôíves vizsgálatok segítsé-gével azonosították, hogy az alexitímia két vetülete, az érzelmek azonosítá-sának nehézsége és -kisebb mértékben -az érzelmek leírásának nehézsé-ge mér sékelt, de szignifikáns mértékben összefügg a disszociatív hajlammal (Berenbaum & James, 1994;Grabe, Rainermann, Spitzer, Gänsicke, & Frey berger, 2000;Irwin & Melbin-Herberg, 1997). Elzinga, Bermond és van Dyck (2002) nagy elemszámú kutatásban a két konstruktum közötti kapcsolat elemzésébe bevonta a gyermekkori abúzus-élményeket, az aktuális stressz szintjét és (az alexitímia faktoraként) a fantáziakészséget is.…”
Section: Disszociatív Kapacitásunclassified
“…Kérdôíves vizsgálatok segítsé-gével azonosították, hogy az alexitímia két vetülete, az érzelmek azonosítá-sának nehézsége és -kisebb mértékben -az érzelmek leírásának nehézsé-ge mér sékelt, de szignifikáns mértékben összefügg a disszociatív hajlammal (Berenbaum & James, 1994;Grabe, Rainermann, Spitzer, Gänsicke, & Frey berger, 2000;Irwin & Melbin-Herberg, 1997). Elzinga, Bermond és van Dyck (2002) nagy elemszámú kutatásban a két konstruktum közötti kapcsolat elemzésébe bevonta a gyermekkori abúzus-élményeket, az aktuális stressz szintjét és (az alexitímia faktoraként) a fantáziakészséget is.…”
Section: Disszociatív Kapacitásunclassified
“…Bernbaum and James (1994) studied the family factors associated with alexithymia. Results demonstrated that those children, who developed in insecure and anxious environments while the emotion detection is prevented, they do not learn the successful coping with emotional situations.…”
mentioning
confidence: 99%
“…Therefore, they become upset by experiencing an emotional situation. These difficulties and lack of appropriate mentor for expressing emotion may lead to anxiety and ambivalence (Bernbaum & James, 1994). Besharat (2010) showed that insecurity in attachment relationship can predict defect and failure to identify and express emotions.…”
mentioning
confidence: 99%
“…Krystal (1988) was probably the first to emphasize that alexithymia is one of the sequelae of traumatic experiences. From research data evidence exists for the idea that psycho-traumata can indeed induce alexithymia (Hyer et al, 1990;Thomas et al, 1992;Berenbaum & James, 1994;Zlotnick, et al, 2001;Frewen et al, 2008). Victims of both rape (Zeitlin et al, 1993) and CSA (Albach & Everaerd, 1992;Berenbaum, 1996;Cloitre et al, 1997;Moormann et al, 1997;Sher & Twaite, 1999;Bermond et al, 2008) are known to suffer from alexithymia.…”
Section: Gender and The Issue Of Credibilitymentioning
confidence: 99%